Diabetes Mellitus, Independent of Body Mass Index, Is Associated With a "Higher Success" Rate for Supraclavicular Brachial Plexus Blocks. Issue 5 (1st August 2009) - Gebhard, Ralf E.; Nielsen, Karen C.; Pietrobon, Ricardo; Missair, Andres; Williams, Brian A.
Abstract : Background and Objectives: The prevalence of obesity and diabetes mellitus continues to rise in industrialized countries. The impact of diabetes on the practice of peripheral nerve block anesthesia, however, has not been fully elucidated. The authors retrospectively evaluated the influence of diabetes, body mass index (BMI), age, and sex on the success of supraclavicular block (SCB) placed with a landmark-based paresthesia technique. Methods: The anesthetic records of 1858 consecutive patients who received an SCB were analyzed. Block success was documented solely on the day of surgery, without additional follow-up. Patients were categorized as diabetic (group D, n = 262) or nondiabetic (group ND, n = 1596). Block "success rate" (ie, general anesthesia not required to produce surgical conditions) was analyzed using multiple regression (multivariable linear and logistic) to assess the associations of diabetes and/or body mass index on successful surgical anesthesia. Results: Patients in group D were more likely (odds ratio, 3.3) to have a "successful" SCB for surgical anesthesia than were patients in group ND ( P < 0.0001). Body mass index, age, and sex were not associated predictors of SCB "success." Conclusions: We speculate that the "higher success" of SCB in patients with diabetes may be explained by: (i) higher sensitivity of diabetic nerve fibers to local anesthetics, (ii) possible unknown intraneural penetration before injection, and/or (iii) preexisting neuropathy with accompanying decreased sensation. In the absence of additional follow-up on these patients, these data should generate outcomes research addressing dose-response curves for patients with diabetes or at risk for diabetes.